Developing UK and Norwegian undergraduate students' conceptions of personal social issues in young adult fiction through transnational reflective exchange. (2nd January 2021) - Syed, Ghazal Kazim; Naylor, Amanda; Rimmereide, Hege Emma; Varga, Zoltan; Alara Guanio-Uluru, Lykke Harmony
ABSTRACT: This article presents the results from an international collaboration between undergraduate students in the United Kingdom and Norway. Using Literature Circles and Google Documents in groups, the students liaised digitally over three young adult novels that are prominent within the UK school curriculum. This study explored the ways in which the students together related and responded to the depiction of social and personal issues in the texts. The themes that emerged as being significant to the undergraduates were gender, racism, social class, power distribution and the portrayal of serious illness. In particular, the students related to the portrayal of issues that they viewed as relevant to themselves and potentially to younger students who might read the novels. The online platform provided them space to discuss issues such as death, racism, inequality, war and contemporary politics as they are represented through the medium of literary texts.